2019
DOI: 10.2147/hmer.s193996
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characterization of the urinary metabolic profile of cholangiocarcinoma in a United Kingdom population</p>

Abstract: Background: Outside South-East Asia, most cases of cholangiocarcinoma (CCA) have an obscure etiology. There is often diagnostic uncertainty. Metabolomics using ultraperformance liquid chromatography mass spectrometry (UPLC-MS) offers the portent to distinguish disease-specific metabolic signatures. We aimed to define such a urinary metabolic signature in a patient cohort with sporadic CCA and investigate whether there were characteristic differences from those in patients with hepatocellular carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Recently, a urinary metabolic signature was proposed to associate with CCA. This signature was capable of distinguishing CCA among other cancer entities including hepatobiliary cancers [55]. It was also recently shown that in the serum, specific metabolites might also embody novel biomarkers to distinguish intrahepatic CCA from HCC, with an AUC of 0.89, 75% sensitivity, and 90% specificity, underlining the power of metabolomic biomarkers in biliary cancer per se [56].…”
Section: Metabolomic Markersmentioning
confidence: 86%
“…Recently, a urinary metabolic signature was proposed to associate with CCA. This signature was capable of distinguishing CCA among other cancer entities including hepatobiliary cancers [55]. It was also recently shown that in the serum, specific metabolites might also embody novel biomarkers to distinguish intrahepatic CCA from HCC, with an AUC of 0.89, 75% sensitivity, and 90% specificity, underlining the power of metabolomic biomarkers in biliary cancer per se [56].…”
Section: Metabolomic Markersmentioning
confidence: 86%
“…These data have previously been included in a larger study characterising the CCA profile of a UK population. [13] ! 6…”
Section: Ethics and Sample Collectionmentioning
confidence: 99%
“…[13] Reverse phase (RP)-UPLC-MS was performed with electrospray ionisation (ESI) in both positive and negative modes. [13] The conditions were optimized using quality control (QC) samples in terms of peak shape, reproducibility and retention time. [13] Tandem mass spectrometry Tandem mass spectrometry (MS/MS) analysis was performed using a quadrupole time-of-flight (TOF) Premier instrument (Waters MS Technologies, Manchester, UK).…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
“…[13] The conditions were optimized using quality control (QC) samples in terms of peak shape, reproducibility and retention time. [13] Tandem mass spectrometry Tandem mass spectrometry (MS/MS) analysis was performed using a quadrupole time-of-flight (TOF) Premier instrument (Waters MS Technologies, Manchester, UK). [13] Collision-induced dissociation (CID) experiments of the QC sample were performed for structural elucidation of detected ions in each ionisation mode.…”
Section: Chromatographic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation